Maternal Aerobic Exercise during Pregnancy Can Increase Spatial Learning by Affecting Leptin Expression on Offspring's Early and Late Period in Life Depending on Gender - Ayfer Dayi; Sinem Agilkaya; Seda Ozbal; Ferihan Cetin; Ilkay Aksu; Celal Gencoglu; Sultan Cingoz; Cetın Pekcetin; Kazim Tugyan; Berkant Muammer Kayatekin; Nazan Uysal (The Scientific World Journal)
Maternal exercise during pregnancy has been suggested to exert beneficial effects on brain functions of the offspring. Leptin is an adipocytokine which is secreted from adipose tissues and has positive effects on learning, memory, and synaptic plasticity. In this study, pregnant rats were moderately exercised and we observed the effects of this aerobic exercise on their prepubertal and adult offsprings' spatial learning, hippocampal neurogenesis, and expression of leptin. All the pups whose mothers exercised during pregnancy learned the platform earlier and spent longer time in the target quadrant. Their thigmotaxis times were shorter than those measured in the control group. It is shown that hippocampal CA1, CA3 neuron numbers increased in both prepubertal and adult pups, in addition that GD neuron numbers increased in adult pups. Leptin receptor expression significantly increased in the prepubertal male, adult male, and adult female pups. In our study, maternal running during pregnancy resulted in significant increase in the expression of leptin receptor but not in prepubertal female pups, enhanced hippocampal cell survival, and improved learning memory capability in prepubertal and adult rat pups, as compared to the control group. In conclusion, maternal exercise during pregnancy may regulate spatial plasticity in the hippocampus of the offspring by increasing the expression of leptin.